Detoxification Therapy in Critical States of Toxic Etiology - Ye. A. Luzhnikov; Yu. S. Goldfarb (Общая реаниматология, 2006)
Objective: to improve the results of detoxification therapy for acute exogenous intoxications. Materials and methods. More than 20 thousand patients with intoxication caused by psychopharmacological agents, organic phosphorus compounds, chlorinated hydrocarbons, and other poisons, in whose treatment enhanced natural detoxification methods, as well as artificial detoxification methods and antidote therapy were used, were examined.Results. Complex detoxification should include efferent methods (hemosorption, hemo- and peritoneal dialysis and intestinal lavage, as well as physiohemotherapy (magnetic, laser, and ultraviolet) and chemohemotherapy with sodium hypochlorite) and should be composed of 2 basic stages: 1) to reduce for a short space of time (1—2 h) the blood poison level to the life-safe one (below the lethal or critical one) that promotes elimination of severe hemostatic disorders, wherein the leading role is played by efferent methods and chemohemotherapy and 2) to terminate a detoxifying process within 1—2 days, which is predominantly associated with the effect of physiohemotherapy as a potent stimulant of natural detoxification and which is achieved just via further stabilization of homeostatic disorders. In the somatogenic stage, detoxification is continued through the program use of physiochemical hemotheraupetic methods and drugs.Conclusion. Introduction of the above principle of complex detoxification performed by a certain algorithm contributes to the higher rate of freeing the blood and urine from exo- and endogenous toxicants by 1.4-12 times and to the significant (more than 2-fold) mortality reduction achieved in an intensive care unit, Moscow City Center of Acute Intoxication Management.